Prediksi Erosi Kebun Kopi Rakyat di Kecamatan Permata, Kabupaten Bener Meriah, Provinsi Aceh - Hairul Basri; Syamaun A. Ali; Konadi Konadi (Department of Agricultural Engineering, Syiah Kuala University, 2012)
Prediction of Erosion in the Coffee Plantation in Subdistrict of Permata, District of Bener Meriah, Province of AcehAbstract. This study aimed to determine the level of erosion that occurred on the slopes of plantation of coffee community in sub-district of Permata, district of Bener Meriah, Province of Aceh, conducted from January to August 2011. Coffee plantations of community were located in sub-district of Permata as samples, particularly in the village of Jungke which had 8 percent slope and the village of Seni Antara which had 30 percent slope. This study was conducted by field observation and laboratory analysis to predict the values of erosion using the method of USLE (universal soil loss equation). Further Erosion Hazard Level (TBE) was determined by considering the effective depth of soil. The results showed that the value of the actual erosion that occurred in the coffee plantation of community in the village of Seni Antara which had 30 percent slope at 87,711.47 tones ha-1 year-1 greater than the actual value of erosion in the village Jungke which only 8 percent slopes at 21.79 tones ha-1 year-1. Erosion Hazard Rate on slopes of 30 percent (village of Seni Antara) classified as very heavy, while TBE at 8 percent slope (Village of Jungke) as light. The main factors that affected the value of erosion were the value of LS (long and large slope) and the value of K (erodibility). To prevent erosion on coffee plantations advised people to be able to add shade trees, use of litter and planting cover crops.